2016
DOI: 10.3390/ijms17040474
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone Modulates Blood Coagulation in Vitro via Its Effects on Inflammatory and Coagulation Pathways

Abstract: Thymoquinone (THQ) is a major component of black seeds. Given that both THQ and black seeds exhibit anti-cancer and anti-inflammatory activities, we hypothesized that THQ will affect cancer-associated thrombosis (CAT), which is primarily triggered by tissue factor (TF) and inflammation. The effect of both black seed-extracted and purchased (“pure”) THQ on normal blood coagulation was tested with in vitro thromboelastography (TEG) and activated partial thromboplastin time (aPTT) coagulation assays. The effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 43 publications
(50 reference statements)
0
15
0
1
Order By: Relevance
“…In vitro coagulation assays of thromboelastography (TEG) and activated partial thromboplastin time (aPTT) using pancreatic cancer cell lines, tested the anticoagulant effect of Thymoquinone of N. sativa and it has been determined that Thymoquinone reversed the cancer-associated thrombosis (CAT) by returning tissue factor (TF) and inflammation to basal levels. Moreover, Thymoquinone inhibited the activity of factor Xa significantly, at higher concentrations (0.8-1.6 mg/mL) [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…In vitro coagulation assays of thromboelastography (TEG) and activated partial thromboplastin time (aPTT) using pancreatic cancer cell lines, tested the anticoagulant effect of Thymoquinone of N. sativa and it has been determined that Thymoquinone reversed the cancer-associated thrombosis (CAT) by returning tissue factor (TF) and inflammation to basal levels. Moreover, Thymoquinone inhibited the activity of factor Xa significantly, at higher concentrations (0.8-1.6 mg/mL) [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was evident that TQ at higher concentrations (5 μM) led to morphological changes and cell death compared to lower concentrations. In the present study, we identified that the IC50 concentration of TQ to be 3 μM based on the mean concentrations from two different assays (MTT and CellTiter-Blue ® ) at 48 h. The concentrations of TQ and their cellular effects varied from 0.1 to 100 μM based on the purity of the compound, the cell types used and the nature of the studies ( Muralidharan-Chari et al, 2016 ; Aziz et al, 2018 ; Bordoni et al, 2019 ).…”
Section: Discussionmentioning
confidence: 90%
“…N sativa , due to its wide range of bioactive components such as TQ and nigellimine, could offer a range of benefits for treating COVID-19, such as blocking the introduction of the virus to pneumocytes; providing ionophores to improve zinc intake, thereby improving the host immune response to SARS-CoV-2; and preventing the virus from replicating. 29 TQ is the main bioactive principle in N Sativa , and this has been found to confer a range of therapeutic advantages 34 including antioxidant, 38 anti-inflammatory, 39 , 46 anticancer, 40 antibacterial, 41 antifungal, 42 anticoagulant, 47 anti-sepsis, 48 and anticonvulsant activity. 43 N Sativa seeds have also demonstrated immunomodulatory effects, 49 , 50 while several studies suggest that N Sativa seeds have some antiviral effects.…”
Section: Potential Beneficial Effects Of Thymoquinone In Covid-19mentioning
confidence: 99%